The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/iai.00760-16
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia pseudotuberculosis Blocks Neutrophil Degranulation

Abstract: bNeutrophils are essential components of immunity and are rapidly recruited to infected or injured tissue. Upon their activation, neutrophils release granules to the cell's exterior, through a process called degranulation. These granules contain proteins with antimicrobial properties that help combat infection. The enteropathogenic bacterium Yersinia pseudotuberculosis successfully persists as an extracellular bacterium during infection by virtue of its translocation of virulence effectors (Yersinia outer prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 56 publications
5
22
0
Order By: Relevance
“…Recently it was shown that Yersinia pseudotuberculosis inhibits neutrophil degranulation in a T3SS-dependent manner, which was dependent on the actions of YopE and YopH (73). Here, we show T3SS-dependent inhibition of neutrophil degranulation by Y. pestis, as well as roles of both YopE and YopH in inhibition.…”
supporting
confidence: 56%
“…Recently it was shown that Yersinia pseudotuberculosis inhibits neutrophil degranulation in a T3SS-dependent manner, which was dependent on the actions of YopE and YopH (73). Here, we show T3SS-dependent inhibition of neutrophil degranulation by Y. pestis, as well as roles of both YopE and YopH in inhibition.…”
supporting
confidence: 56%
“…To the best of our knowledge, the immediate pattern of exocytosis of human neutrophil granules is unique to M. smegmatis. While other bacteria have been shown to block or induce degranulation of some or all neutrophil granule subtypes [32,[49][50][51][52][53][54][55][56][57][58][59], release of only gelatinase granules at early time points has not been seen with bacteria other than M. smegmatis. An important distinction is that M. smegmatis is not preventing granule release to other stimuli, since granule mobilization was not affected upon fMLF stimulation by human neutrophils cultured with M. smegmatis.…”
Section: Discussionmentioning
confidence: 99%
“…After neutrophil migration, degranulation occurs, which is the process mediated by microbial or inflammatory stimuli in which neutrophils release the granule contents, such as MPO, defensins, cathepsin G, neutrophil elastase, and collagenase. These granule contents are released by exocytosis or into the phagosome to kill microorganisms [24].…”
Section: Actions Of Neutrophils In Infected Sitesmentioning
confidence: 99%